The Quality and Visual Character of Thematic Village as a Tourist Attraction in Malang City - Shallikha Rizkia Masrifa; Indyah Martiningrum (Jurnal Mahasiswa Jurusan Arsitektur, 2020)
The concept of a thematic village is to create a village space with certain characteristics by the community. Kampung Tridi and Kampung Warna-Warni, which are connected by Jembatan Kaca, as tourist destinations have a similar theme, namely updating the village visuals by painting residents' houses with attractive colors resulting in many tourists coming to visit. However, visitors only take pictures in certain photo objects so that each photo object has a different visual appeal. The purpose of this study was to evaluate the visual quality based on the perceptions of visitors and identify the visual characters that are the attractiveness of the thematic village. This study uses a combined method with a sequential explanatory strategy. The data were collected by means of observation, documentation, interviews and questionnaires. The research was continued with a descriptive statistical analysis process to calculate the results of the evaluation of visual quality based on visitor perceptions and continued with a qualitative descriptive analysis to compare the visual elements that represented the characters of each photo object. The results showed that the visual quality of Kampung Tridi, Kampung Warna-Warni and Jembatan Kaca was considered good in terms of the seven observation units based on the results of the questionnaire. However, the observation unit with a very positive value only consists of the diversity and dominance in the field block and the uniqueness of the Jembatan Kaca block so that the character which has high attractiveness is formed by the three observation units.